Adaptive memory: The effects of survival-constrained retrieval on recognition depend on initial encoding conditions. - Bell, Raoul; Mieth, Laura; Kroneisen, Meike (Memory & Cognition, 2026)
Information relevant to survival has been found to be prioritized in memory, a finding often interpreted as reflecting evolved mnemonic mechanisms. While much research has focused on survival processing at encoding, the effect of constraining retrieval to the survival condition on later memory performance remains less well studied. Two experiments serve to examine whether survival-constrained retrieval in an intermediate source-constrained retrieval test impairs or improves recognition of words in a final memory test, depending on whether intermediate retrieval was constrained to the condition in which the words were initially encoded. Two competing hypotheses are evaluated: The retrieval-based interference account predicts that survival-constrained retrieval may blur the distinction between words initially judged for survival relevance and foils introduced in the intermediate source-constrained retrieval test, leading to impaired final recognition. In contrast, the retrieval-based strengthening account suggests that survival-constrained retrieval strengthens memory for the words initially judged for survival relevance, relative to words encoded in a control condition. Across two experiments using survival, pleasantness, or moving relevance judgments at initial encoding and intermediate source-constrained retrieval, final recognition was consistently better when intermediate retrieval was constrained to the initial encoding condition. The results contribute to the adaptive-memory framework by showing that survival-related memory advantages are shaped by both initial encoding and intermediate retrieval processes.